Analysis of recent merger and acquisition activities in Singapore : predictive of near-term outlook? - Tan, Benjamin Siong Guan. (2008)
This paper concentrates on Singapore M&A by analyzing the patterns thereof during the period 1997-2002. When the sixth global merger wave arrives, Singapore will likely register the highest level of deals in the electronics manufacturing, finance and communications industries.